Fine‐mapping of a novel premenopausal breast cancer susceptibility locus at Chr4q31.22 in Caucasian women and validation in African and Chinese women. Issue 5 (27th May 2019) - Kumaran, Mahalakshmi; Ghosh, Sunita; Joy, Anil A.; Mackey, John R.; Cass, Carol E.; Zheng, Wei; Yasui, Yutaka; Damaraju, Sambasivarao
Abstract : We previously identified a novel breast cancer susceptibility variant on chromosome 4q31.22 locus (rs1429142) conferring risk among women of European ancestry. Here, we report replication of findings, validation of the variant in diverse populations and fine‐mapping of the associated locus in Caucasian population. The SNP rs1429142 (C/T, minor allele frequency 18%) showed association for the overall breast cancer risk in Stages 1–4 ( n = 4, 331 cases/4271 controls; p = 4.35 × 10 −8 ; odds ratio, ORC‐allele, 1.25), and an elevated risk among premenopausal women ( n = 1, 503 cases/4271 controls; p = 5.81 × 10 −10 ; ORC‐allele 1.40) in European populations. SNP rs1429142 was associated with premenopausal breast cancer risk in women of African (T/C; p ‐value 1.45 × 10 −02 ; ORC‐allele 1.2) but not from Chinese ancestry. Fine‐mapping of the locus revealed several potential causal variants which are present within a single association signal, revealed from the conditional regression analysis. Functional annotation of the potential causal variants revealed three putative SNPs rs1366691, rs1429139 and rs7667633 with active enhancer functions inferred based on histone marks, DNase hypersensitive sites in breast cell line data. These putative variants were bound by transcription factors (C‐FOS, STAT1/3 and POL2/3) with known roles in inflammatory pathways. Furthermore, Hi‐C data revealed several short‐range interactions in the fine‐mapped locus harboring the putative variants. The fine mapped locus was predicted to be within a single topologically associated domain, potentially facilitating enhancer–promoter interactions possibly leading to the regulation of nearby genes. Abstract : What's new? To date, genome‐wide association studies have addressed familial or postmenopausal breast cancer susceptibility variants. However, genetic predisposition for sporadic premenopausal breast cancer risk is unknown. This study reports a novel variant (at 4q31.22) associated with elevated risk for premenopausal breast cancer among women from European and African ancestry. The fine‐mapped locus was predicted to be within a single topologically associated domain, potentially facilitating enhancer‐promoter interactions leading to the regulation of nearby genes.